2013
DOI: 10.1007/s00264-013-1870-0
|View full text |Cite
|
Sign up to set email alerts
|

Posterior acetabular arc angle of the femoral head assesses instability of posterior fracture-dislocation of the hip

Abstract: Purpose Unstable posterior fracture-dislocation of the hip is determined by the wall defect or acetabular fracture index. The unstable hip is a result of inadequate posterior acetabular coverage of the femoral head from the posterior acetabular wall fracture. In order to measure total posterior acetabular coverage of the femoral head and avoid using the contralateral acetabulum as a calculation reference, the posterior acetabular arc angle of the femoral head was measured to assess stability of posterior fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…The study showed 54.48°coronal PAAA of the unstable posterior hip fracture-dislocation and 57.43°of 50 % of the posterior wall of the normal contralateral posterior acetabulum, with no statistically significant difference (Table 1). Moreover, coronal PAAA and 50 % of the posterior acetabular wall corresponded to the study by Harnroongroj et al [6]. Measuring vertical PAAA of the posterior acetabular wall fracture in the vertical plane using 3D CT reconstruction of the lateral pelvis may be another beneficial method for more detailed evaluation of the unstable posterior hip fracture-dislocation.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The study showed 54.48°coronal PAAA of the unstable posterior hip fracture-dislocation and 57.43°of 50 % of the posterior wall of the normal contralateral posterior acetabulum, with no statistically significant difference (Table 1). Moreover, coronal PAAA and 50 % of the posterior acetabular wall corresponded to the study by Harnroongroj et al [6]. Measuring vertical PAAA of the posterior acetabular wall fracture in the vertical plane using 3D CT reconstruction of the lateral pelvis may be another beneficial method for more detailed evaluation of the unstable posterior hip fracture-dislocation.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, patients 17 and 18 shown in Table 1 displayed 75°and 76°coronal PAAA, respectively, with a 22.42-and 24.60-mm coronal posterior wall, respectively. Both cases had clinical unstable posterior hip fracture-dislocations, which did not show on the images [4,6]. On the other hand, both cases had outstanding 119°and 112°of vertical PAAAs of the wall fracture compared with 120°and 118°of intact vertical PAAA of normal contralateral acetabulum (Table 2).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Acetabular fracture involving superior weight bearing area shows significantly poor results 12. Moreover, stability of the hip depends on adequate acetabular coverage of the femoral head 34. Roof arc angle is a method to evaluate adequate acetabular coverage and stability of the femoral head, Matta and Merritt study based on clinical findings and suggested that the fracture crosses acetabular weight bearing dome when <45° medial, anterior and posterior roof arc angles 56.…”
Section: Introductionmentioning
confidence: 99%